AGROCHEMICAL EXPOSURE AND PEDIATRIC LEUKEMIA: A NARRATIVE REVIEW - Inna Armandari; Miratul Hasanah (Fakultas Kedokteran Hewan Universitas Udayana, 2026)
Pediatric leukemia is the most common childhood cancer worldwide, with acute lymphoblastic leukemia (ALL) and acute myeloid leukemia (AML) representing the majority of cases. Although genetic susceptibility contributes to disease development, it explains a minority of cases, emphasizing the potential role of environmental exposures in the pathogenesis. Among these, agrochemicals, including pesticides, herbicides, and insecticides, are extensively used in agricultural and residential settings and have been widely investigated of their biological plausibility for carcinogenic effects through mechanisms such as genotoxicity, oxidative stress, endocrine disruption, and epigenetic alteration. This narrative review synthesizes evidence on the association between agrochemical exposure and pediatric leukemia from systematic reviews, meta-analyses, and observational studies. Overall, the literature consistently reports modest but positive associations between pesticide exposure and childhood leukemia, particularly ALL. Stronger associations are observed for maternal prenatal, residential pesticide use, and early-life exposure. Evidence also indicates increased risk associated with paternal occupational exposure near conception, maternal occupational exposure during pregnancy, indoor insecticide use, and certain classes of insecticides and herbicides. Residential proximity to agricultural areas has been linked to higher incidence, potentially reflecting pesticide drift. Despite consistent findings, limitations remain, including heterogeneity in exposure assessment, reliance on self-reported data, and predominance of observational designs. Future studies should incorporate prospective designs, biomarker-based exposure measurement, and improved geospatial modeling to strengthen causal inference, clarify risk magnitude, and inform preventive strategies.